Effectiveness of opioid maintenance programs for treating drug dependence in prisons - Salma Roselló-Jordá; Carla Espinós-Navarro; María Pilar Molés-Julio (Sociedad Española de Sanidad Penitenciaria, 2024)
Abstract Objectives: To evaluate the effectiveness of opioid maintenance programs in treating opioid dependence in Spanish prisons. Material and method: A narrative bibliographic review was carried out on the following databases: PubMed; Cochrane; IBECS; LILACS; HealthCare. All clinical trials were chosen as a preference, along with systematic review articles and some articles that were considered relevant for their content. The time period was limited to between January 2011 and November 2021. The languages chosen were English, Spanish and Catalan. Repeated articles and those that were not related to the objectives were rejected. The search criteria were: "methadone AND prisons"; "opiate substitution treatment AND prisons"; "methadone AND buprenorphine"; "methadone OR buprenorphine"; "prisons AND Methadone AND buprenorphine". Results: 20 articles were selected out of 647 items consulted after applying the corresponding filters and after discarding duplicates. Discussion: There was a slightly greater effectiveness of buprenorphine versus methadone. The high prevalence of the program was highlighted, as well as the variety of adverse effects of methadone. Usefulness with regard to inmates' behavior showed a range of opinions. The possibility of new treatment alternatives with better pharmacological control is mentioned.